Impacts of Wildfires on School Children: A Case Study of Slave Lake, Alberta, Canada. Issue 2 (August 2015) - Townshend, Ivan; Awosoga, Olu; Kulig, Judith; Botey, Anna Pujadas; Shepard, Blythe; McFarlane, Bonita
Wildfires are becoming increasingly common, but there is limited understanding of their effects on children. This article reports on a study of wildfire impacts on children in a Canadian community. Self-reported measures of posttraumatic stress and coping and behavioral difficulties were obtained from a school-based survey of children in grades three to 12 carried out six months (T1) and 12 months (T2) after the fires. Students completed two screening instruments: the University of California at Los Angeles Post-traumatic Stress Disorder (PTSD) Reaction Index for Children and Adolescents – DSM-IV-TR, and the Strengths and Difficulties Questionnaire, and provided information about demographic details and loss of their home. Paired data (n = 140) revealed that a substantial number of children met certain PTSD criteria symptoms at T1 but the number declined by T2. Differences in symptoms by age, gender, and house loss were examined. Age and house loss were important differentiators of impact, but these waned through time, and house loss was not a defining trait of those most at risk of severe psychopathology. Future research examining children's responses to a variety of disasters would add to our knowledge about stress reactions while determining whether there are commonalities in responses across types of disasters.